2021
DOI: 10.1590/0001-3765202120200632
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genetic toxicity of sofosbuvir and simeprevir with and without ribavirin in a human-derived liver cell line

Abstract: Direct-acting antivirals have revolutionized the treatment of chronic hepatitis C. Sofosbuvir and simeprevir are prescribed worldwide. However, there is a scarcity of information regarding their genotoxicity. Therefore, the present study assessed the cytotoxic and genotoxic effects of sofosbuvir and simeprevir, alone and combined with ribavirin. HepG2 cells were analyzed using the in vitro cytokinesis-block micronucleus cytome assay. Cells were treated for 24 h with sofosbuvir (0.011−1.511 mM), simeprevir (0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Recent in vitro models showed that sofosbuvir (SOF) and daclatasvir (DCV) drugs impaired mitochondrial morphologies and lowered the mtDNA copy number in yeast [ 3 ]. Furthermore, the association of sofosbuvir and ribavirin (RBV) increased cytotoxicity in HepG2 cells [ 6 ]. We recently investigated mitochondrial genotoxicity among people who inject drugs (PWID) who were treated with a combination of SOF, DCV, and RBV drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro models showed that sofosbuvir (SOF) and daclatasvir (DCV) drugs impaired mitochondrial morphologies and lowered the mtDNA copy number in yeast [ 3 ]. Furthermore, the association of sofosbuvir and ribavirin (RBV) increased cytotoxicity in HepG2 cells [ 6 ]. We recently investigated mitochondrial genotoxicity among people who inject drugs (PWID) who were treated with a combination of SOF, DCV, and RBV drugs.…”
Section: Introductionmentioning
confidence: 99%